Pusat Batik Banyumasan dengan Pendekatan Kearifan Lokal di Purwokerto - Aqmarina Safitri; Rachmadi Nugroho; Hari Yuliarso (ARSITEKTURA, 2017)
Batik became one of Indonesia’s cultural heritage that should be preserved and cultivated batik is already recognized by the international community (UNESCO) designated as a Masterpieces of the Oral and Intangible Heritage of Humanity. Purwokerto is a batik producer Banyumasan which have tourism potential of batik spreads make travelers less efficient in time to reach the points the location of batik industry. The problems that arise in the design of the center of Batik Banyumasan in Purwokerto is how efforts to plan and design a Banyumasan Batik Center that hostsrelated activities efficient batik tour for tourists. The aim is to meet the container activities related to information and promotion, sales, and production of Banyumasan Batik with the approach of Local Wisdom. Architectural design that fits this batik center planning method using Local Wsdom aspect due to the approach of considering the aspects of Local Wisdom that still exists in the local environment. The concept of a Batik Centre Local Wisdom will apply to wards the building that includes the concept of a zone of space, building orientation, shape and appearance of the building as well as the structure of the building is closely related to the element of local wisdom. Keywords:Batik, Banyumasan Batik, Batik Center, Purwokerto, Local Wisdom.